Analisis Implementasi Akuntansi Manajemen terhadap Pengendalian Biaya Produksi pada PT Garudafood Putra Putri Jaya Tbk - Anisah Rusnadi; Feby Dwi Lestari; Zahreyski Pardiansyah; Titania Zahra Nurliyan (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
The purpose of this study is to examine how PT Garudafood Putra Putri Jaya Tbk uses management accounting to support production cost control between 2020 and 2024. Using secondary data from the company's financial records and official publications of the Indonesia Stock Exchange (IDX), a descriptive qualitative research methodology was employed. This study's primary goal is to determine how much operational effectiveness and business profitability can be increased by implementing management accounting strategies such responsibility accounting, activity-based costing, variance analysis, and budgeting.. The findings reveal that the management accounting system applied by PT Garudafood plays a vital role in helping management identify sources of inefficiency, optimize resource utilization, and improve data-driven decision-making. Budgeting serves as an effective planning and control tool, while variance analysis is used to evaluate differences between actual and budgeted costs to determine corrective actions. The application of ABC allows the company to allocate overhead costs more accurately based on production activities, whereas responsibility accounting strengthens accountability and performance within each work unit. However, the company still faces challenges such as fluctuations in raw material prices, limitations in accounting information systems, and supply chain complexity. Overall, this study concludes that the effective implementation of management accounting significantly enhances cost efficiency, profitability, and the long-term sustainability of PT Garudafood in an increasingly competitive food industry.